Scientific skills research improvements for young teachers in today’s Colleges and Universities - Cuong, Nguyen Ngoc (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2018)
Speeding up scientific research is an objective requirement and one of the basic functions and a main purpose of colleges and universities in the national education system where young teachers participate actively in scientific research it is one of the important measures to improve teaching quality and scientific research and to meet the increasing demands of the education and training renewal. The article focuses some on the basic scientific research skills and proposed organizational measures fostering scientific research skills among young teachers in universities and colleges today.